The importance of organizational Justice as an intermediate variable between the academic leadership and Quality of international Performance - Alwhb Jaber, Maidean Abad (Opción, 2019)
Organizational Justice is concerned with all matters of workplace behavior, from treatment by superiors to pay, access to training and gender equality. It is originally derived from equity theory, which suggests individuals make Judgements on fairness based on the amount they give (input) compared to the amount they get back (output). The researcher aims to develop a model that links the research variables and verifies its credibility through the ba- sic hypotheses of research and diagnoses the level of academic leadership practices in the tourism education institutions. The sample of the research is through organizational justice and the extent to which this relationship af- fects the quality of the performance of these institutions by distributing 72 questionnaire forms on them. The study methodology can be summarized by diagnosing (relationship and impact) the academic leadership dimensions and organizational justice dimensions on the quality of the institutional per- formance of a sample of educational institutions in Iraq. A set of hypotheses, main and subsidiary, are established, and the researcher depends on the ques- tionnaire in addition to other methods, such as personal interviews of deans, assistants, heads of departments, and employees of the surveyed institutions. A number of statistical methods were used: the weighted mathematical mean, the standard deviation, the determining factor, the exploratory analysis. The Scientific value of the research lies in that the presentation of the results of the study of the relationship between the main variables will explain the strengths and weaknesses of decision makers, which can be used and applied in the institutions investigated, and on the other hand, the institutions investigated may be in an urgent need of data in this stage, which can be provided by the research in the way that serves the future orientation to reach high efficiency on the level of all outputs of these institutions. As for the results, the researcher reached a number of conclusions, the most important of which proved that academic leadership through its di- mensions play an important role for the teachers in raising the level of performance and improvement and to ensure a high level of excellence for these institutions. The most important recommendations were to involve teachers and staff in decision-making, to take care of all their affairs and needs and to meet their requirements, in order to build their sense of be- longing and to strengthen the spirit of loyalty to institutions and work in them.